EXPERIMENTAL JUSTIFICATION OF DESIGN DEVICES FOR ELECTROCHEMICAL PROPERTIES CHANGES OF AQUEOUS SOLUTIONS (FOR EXAMPLE GALVANIC) - Shtepa, V.; Cot, R (Енергетика і автоматика, 2016)
Analyzed the existing structure electrolysis plants, considered scientific approaches regarding their structural and technological classification in solving the problem of electrochemical changes in the properties of water has dissolved. The features of electroplating wastewater treatment plants; set which tasks should be decided by such equipment. On the model aqueous solution set of design features electrolysis wastewater treatment plants electroplating; The resulting pattern confirmed at the wastewater real line plating. The conclusions regarding the intensification of additional equipment functioning electrolysis plants change the properties of aqueous solutions.